1998
DOI: 10.1046/j.1365-3059.1998.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phytoplasmas infecting winter oilseed rape in the Czech Republic with Italian Brassica phytoplasmas and their relationship to the aster yellows group

Abstract: Winter oilseed rape grown in several areas in South Bohemia showed symptoms of stunting, leaf reddening and extensive malformation of floral parts. Phytoplasmas were consistently observed by using electron microscopy only in phloem tissue of symptomatic plants. DNA isolated from infected and healthy control plants was used in PCR experiments. Primer pairs R16F2/R2, P1/P7 and rpF2/R2, amplifying, respectively, 16S rDNA, 16S rDNA plus spacer region and the beginning of the 23S and ribosomal protein gene L22 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
4
26
0
3
Order By: Relevance
“…Phytoplasma pathogens that infect rapeseed/canola in Canada, Czech, Italy and Greece (Bertaccini et al 1998;Maliogka et al 2009;Olivier et al 2006;Wang and Hiruki 2001), identified as the 16SrI aster yellows group, cause stunting, leaf yellowing or purpling. None of these symptoms have been observed on toria in India, which is infected with the 16SrIX pigeon pea witches'-broom group phytoplasma (Azadvar et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplasma pathogens that infect rapeseed/canola in Canada, Czech, Italy and Greece (Bertaccini et al 1998;Maliogka et al 2009;Olivier et al 2006;Wang and Hiruki 2001), identified as the 16SrI aster yellows group, cause stunting, leaf yellowing or purpling. None of these symptoms have been observed on toria in India, which is infected with the 16SrIX pigeon pea witches'-broom group phytoplasma (Azadvar et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These sequences were compared with each other and with those already reported in the database. 16S rDNA sequence analysis revealed that ROL-Ph is most closely related to onion yellows (OY) phytoplasma from Japan (Namba et al, 1993a) and rape phyllody (Rhp) phytoplasma from the Czech Republic (Bertaccini et al, 1998), both of which belong to the aster yellows subgroup of the AY 16S-group (Jung et al, 2002). Judging from the 16S rDNA sequence similarity between ROL-Ph and OY (99?9 %), Rhp (99?8 %) and the other aster yellows subgroup members (98?9-99?8 %), it is reasonable to classify the ROL phytoplasma in the AY 16S-group, thus distinguishing it from RYD, which belongs to the RYD 16S-group (Jung et al, 2002).…”
mentioning
confidence: 99%
“…All these phytoplasmas belong to 16SrIX phytoplasma group. Phytoplasma associated with oilseed brassicas in Canada, Czech Republic, Italy and more recently in Greece on the other hand belonged to 16SrI group [4,16,20,28]. Further study involving in silico analysis and virtual RFLP of 16S rDNA sequence including the application of iPhyClassifier indicated that all the four Indian isolates of TP phytoplasma were identical and belonged to 16SrIX-C phytoplasma subgroup and this was further supported by phylogenetic analyses of 16S rRNA, rp genes and 16S-23S rRNA intergenic region spacer sequences.…”
Section: Discussionmentioning
confidence: 65%
“…The incidence of infection by phytoplasmas based on symptoms expressed in different accessions of toria was variable and reached 11% in toria field in New Delhi over a period of 2 years [2]. The major symptoms of phytoplasma diseases of toria consisted of virescence, phyllody and formation of hollow bladders but not stunting, leaf yellowing or purpling as reported for phytoplasma infected oilseed brassicas in other countries [4,16,20] indicating that the phytoplasmas associated with toria phyllody might be distinct from phytoplasmas infecting brassicas in other countries. Comparison of 16S rRNA gene sequence of toria phyllody showed that the toria phyllody phytoplasma shared maximum identity of 99% to that of K. arvensis phyllody (Y18052) from Italy and Khafr (Iran) almond witches'-broom phytoplasma (DQ195209) from Iran.…”
Section: Discussionmentioning
confidence: 99%